Conflicto y desmovilización en la Argentina del Cordobazo: Un análisis comparativo de FIAT Concord Córdoba y FIAT Palomar Buenos Aires, 1969-1972 - Laufer, Rodolfo (2020)
This article makes a comparative analysis between the different worker experiences developed in two company unions of the Fiat Group in Argentina in the period after Cordobazo (1969). While at the SITRAC, in the Concord plant in Córdoba, there was a strong unrest and a confrontational and radicalized trade union action (clasismo), at the SITRAFIC, in the Palomar plant in Buenos Aires, the conflict was limited and remained the predominance of a negotiating and conciliatory unionism (vandorismo). In order to explain these different trajectories, we analyze the union experiences of both working groups and the relationship between both processes.